A comparative study of memory‐type control charts under normal and contaminated normal environments. (7th July 2015) - Nazir, Hafiz Zafar; Abbas, Nasir; Riaz, Muhammad; Does, Ronald J.M.M.
Abstract : Cumulative sum (CUSUM) and exponentially weighted moving average (EWMA) control charts are commonly used to detect small changes in the parameters of production processes. Recently, a new control structure was introduced, named as mixed EWMA–CUSUM control chart, which combined both charts. The current study provides a detailed comparison of these three types of control charts when the process parameters are unknown under normal and contaminated normal environments. Performance measures average run length and different percentiles of run length distribution are used for comparison purposes. We investigate six different location estimators with the structures of the three memory charts and study their robustness properties. Copyright © 2015 John Wiley & Sons, Ltd.